Anti–Citrullinated Protein Antibody Specificities, Rheumatoid Factor Isotypes, and Incident Cardiovascular Events in Patients With Rheumatoid Arthritis. Issue 10 (7th September 2020) - Westerlind, Helga; Rönnelid, Johan; Hansson, Monika; Alfredsson, Lars; Mathsson‐Alm, Linda; Serre, Guy; Cornillet, Martin; Holmdahl, Rikard; Jakobsson, Per‐Johan; Skriner, Karl; Klareskog, Lars; Saevarsdottir, Saedis; et al.
Abstract : Objective: To investigate the relationship between anti–citrullinated protein antibodies (ACPAs), specific ACPA subspecificities, rheumatoid factor (RF) isotypes, and incident cardiovascular (CV) events in patients with rheumatoid arthritis (RA). Methods: Serum samples from Swedish patients with new‐onset RA (diagnosed within 1 year of symptom onset between 1996 and 2009) were centrally typed for anti–cyclic citrullinated peptide 2 (anti‐CCP2) antibodies, 20 ACPA subspecificities, and RF isotypes. Patients were followed up longitudinally in nationwide registers to monitor the occurrence of acute coronary syndrome (ACS), stroke, CV‐related death, and major adverse CV events (MACE). The association between each serologic marker and CV outcome, and the impact of adjustment for the Disease Activity Score in 28 joints (DAS28), smoking status, and income at baseline, were assessed using Cox proportional hazards models. In addition, associations of serologic markers with all‐cause mortality were explored. Results: In total, 2, 814 patients with RA were included in the study. The median follow‐up was 13 years, during which the CV end points of ACS, stroke, or CV‐related death were reported to occur in 375 patients. Occurrence and/or levels of anti‐CCP2 were associated with risk of incident ACS (hazard ratio [HR] 1.46, 95% confidence interval [95% CI] 1.03–2.06), stroke (HR 1.47, 95% CI 1.03–2.10), CV‐related death ( P = 0.024 for association with anti‐CCP2 levels), and MACE (HR 1.34, 95% CI 1.06–1.70). Similarly, an association with the number of ACPA subspecificities was observed; however, this could not be attributed to any individual or group of ACPA subspecificities. Presence of IgM‐RF was associated with all CV end points except ACS, and IgA‐RF was exclusively associated with CV‐related death. Adjustment for smoking status, income, and DAS28 scores decreased most of the HRs, whereas IgA‐RF remained associated with CV‐related death (HR 1.61, 95% CI 1.05–2.48). All of the assessed serologic makers were associated with all‐cause mortality. Conclusion: RF isotypes and ACPAs are associated with future CV events in patients with RA. ACPA levels and number of subspecificities seem more important than the occurrence of particular subspecificities, and these associations were not explained by a history of ever smoking.